Meconial fill - Torres, David Héctor (Cirugía del Uruguay, 1973)
The term Meconium Ileus refers to three different conditions of similar pathologic anatomy and clinical features. but very different prognosis and ·treatment. The author describes: 1) Classic Meconium Ileus and its complications being an affection of high inmediate, mediate and late mortality. 2) The Meconium Plug Síndrome of easy resolution and good prognosis when ever correct diagnosis is established. 3) Meconium obstruction in the absence of mucoviscidosis a rare afection associa ted with intestinal absortive anomalies and whose prognosis is better than of Classic Meconium Ileus.